Downregulation of BDH2 modulates iron homeostasis and promotes DNA demethylation in CD4+ T cells of systemic lupus erythematosus - Zhao, Ming (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2017 Elsevier Inc. All rights reserved.